IBN ‘ARABI’S HADITH PERSPECTIVE IN HIS WORK MISHKAT AL-ANWAR - Ahmad Nabil Amir; Tasnim Abdul Rahman (AL ISNAD: Journal of Indonesian Hadith Studies, 2025)
The paper analyzes Muhyīddīn Ibn ‘Arabī’s (1165-1240) seminal work Mishkat al-Anwar fima Ruwiya ‘an Allah min al-Akhbar (101 Divine Sayings) that compiled profound work of sacred hadith (hadith qudsi) as directly reported by the Prophet (saw) from God. It aims to survey its theological impact and postulate pertaining to the mystical ideas of God, which brought forth diverse religious themes underlying its arguments pertaining to the moral and religious values and symbols that constituted basic ritual and legal practice and its spiritual and mystical implications as highlighted by the Great Master Shaykh al-Akbar throughout this work. The study is based on qualitative method in the form of library and literature survey. It uses descriptive, analytical, philosophical and historical approaches to collectively process the data derived from primary and secondary sources that were further objectively and scientifically analyzed. The study concludes that the work Mishkat al-Anwar (The Divine Reports) portrays significance ideas and understanding of sacred hadith (hadith qudsi) and its broad ethico-legal and mystical conception in light of the synthetic ideology it brought forth that synthesize dogmatic orthodoxy and liberal sufi tradition. It set forth profound metaphysical and eschatological principle and value as well as its spiritual aspect and dimension in light of prophetic guidance derived from revealed law and its sacred interpretation and viewpoint. It reflected unprecedented allegorical and mystical connotation of the Divine Sayings, in light of the Word of God that inspired the light of prophetic reality and its metaphysical manifestation.